Genetic variability, heritability and genetic advance of yield and yield contributing characters of lablab bean (Lablab purpureus L.) - Asaduzzaman, M; Bhuiyan, MJH; Hossain, MA; Raffi, SA (Progressive Agriculture, 2015)
Studies on genetic variability, heritability and genetic advance were carried out with 14 genotypes of Lablab bean (Lablab purpureus L.) cultivated at the Agro-ecological zone9 (AEZ-9) comprising the Old Brahmaputra Floodplain Soil. Considerable amount of genotypic and phenotypic coefficient of variation was observed for all characters studied. Phenotypic variation was greater than that of the genotypic variations for all the characters. The greater portion of total phenotypic variation was due to the genotypic variation. Highest genetic and phenotypic variation were observed for green pod yield per plant (1882.68 and 2108.43, respectively) and 100-green seed weight (1380.91 and 1452.07, respectively) Heritability values were higher for days to maturity (81.37) , number of raceme per plant (80.62), pod length (99.43), pod width (99.27), green pod yield per plant (89.29), dry shelling percentage (91.58), seed yield per plant (84.93) and protein content (98.11) indicating the better potentials of improving these characters for improvement of yield. Maximum genetic advance expressed as percentage of mean was recorded for green pod yield per plant (95.22). Progressive Agriculture 26:22-25, 2015